Ultrasonic behaviour of binary liquid mixtures containing n-octanol as a common component - GOPAL, K.; REDDY, B. Rajeswara; RAO, N. Prabhakara (Archives of Acoustics, 1986)
Ultrasonic wave propagation in binary liquid mixtures of benzene, tolune, O-xylene and ethyl-benzene in n-octanol was studied at 313.16 K. The compressibilities, available volumes, freelengths, relative associations, molar sound velocities and molar compressibilities were calculated from the density and velocity measurements. The systems studied show non-ideal behaviour and the deviations from linearity are explained on the basis of molecular dissociation of n-octanol in the solvents. The sound velocities in these systems have also been calculated theoretically, based on the Free Length Theory (FLT) due to Jacobson and Collision Factor Theory (CFT) due to Schaaffs.